An integrated targeted metabolome of phytohormones and transcriptomics analysis provides insight into the new generation of crops: Polygonatum kingianum var. grandifolium and Polygonatum kingianum - Ning, Luyun; Xiao, Qian; Tan, Chensi; Gong, Limin; Liu, Yeman; Wang, Zhi; He, Shujin; He, Chengdong; Yuan, Hanwen; Wang, Wei (Frontiers in Plant Science, 2024)
Huangjing is becoming a new generation of crop. Polygonatum kingianum var. grandifolium (XHJ) was the variant of P. kingianum (DHJ), and them were treated as Huangjing. Unlike other Polygonatum species, the rhizome bud of XHJ could germinate both in spring and autumn, which contribute to its high rhizome yield.However, molecular mechanism of the autumn shooting of XHJ was still unknown. In the present study, cellular observation, comparative targeted metabolome of phytohormones and transcriptome analysis between XHJ and DHJ in autumn were conducted. Interestingly, 'Diterpenoid biosynthesis' (ko00904) and 'Plant hormone signal transduction' (ko04075) were commonly enriched by differentially accumulated phytohormones (DAPs) and differentially expressed genes (DEGs) in all tissues, which indicated the high Auxin content, low CTK content and low ABA/GA ratio might contribute to the XHJ rhizome buds' differentiation and germination in autumn.Moreover, according to the weighted gene co-expression network analysis (WCGNA), transcript factors (TFs) related to Auxin, CTK, GA and JA metabolism were screened, such as AP2/ERFs, WRKY and NAC, which deserved further research. In conclusion, we comprehensively illustrated the mechanism of XHJ natural autumn shooting by cytological, metabolic and transcriptomic analysis, which would improve our understanding of the high-yield of XHJ rhizomes and the diversity of shooting mechanisms in Polygonatum, to lay the foundation for the further development of Huangjing industry.